Molecular Identification and Phylogenetic Analysis of Fungi Contaminants Associated with In Vitro Cultured Banana Based on ITS Region Sequence - David Adedayo Animasaun; Chinaza Davies Nnamdi; Omotola I. Ipinmoroti; Stephen Oyedeji; Emmanuel A. Olonya; Ramar Krishnamurthy; Joseph Akintade Morakinyo (Bogor Agricultural University, Indonesia, 2022)
This study characterized, identified and conducted phylogenetic analysis on fungi contaminants in vitro bananas based on the sequence of inter-space (ITS) regions. Genomic DNA was extracted from the pure culture of fungi contaminants, amplified and sequenced using ITS1 and ITS4 markers. Analysis of the sequences using MEGA 7 Software at higher similarity sequence identified five Aspergillus spp., three Penicillium spp., one each of Fusarium, Trichoderma and Cladosporium as the contaminants. The genetic distance between the fungi species was 0.205, which suggests a homogeneous substitution between the sequences, and thiamine was the most stable. The fungi clustered in three major groups at 0.10 genetic distance, subdivided into five clusters. A cluster and sub-cluster consisting of five Aspergillus strains; a major cluster of three Penicillium strains; a cluster comprising of Fusarium chlamydosporum and Trichoderma viride; and a sole fungi Cladosporium tenuissimum. The Aspergillus group were phylogenetically related to A. flavus and A. parvissclerotigenus, the identified Penicillium spp. were closely related to Penicillium citrinum while the detected Cladosporium aligned with Cladosporium tenuissium and Phoma multirostrata. The information provided by this study could be utilized to develop a specific and compelling sterilization protocol to minimize the rate of contamination during in vitro culture procedures.